PERDAGANGAN ORANG: KEJAHATAN TERHADAP KEMANUSIAAN - Fofid, Elisabet Maria; Peni, Mathildis (UNIKA Santo Thomas, 2025)
Human trafficking constitutes a complex and systemic crime against humanity, involving serious violations of fundamental human rights. This article analyzes the issue through the lens of applied ethics, grounded in the Catholic Church’s social teachings and the principles of liberation theology. Employing an interdisciplinary approach encompassing legal, social, theological, and pastoral dimensions this study identifies structural factors such as poverty, gender inequality, migration, and weak social protection systems as root causes. The Church is positioned as a prophetic actor with a moral responsibility to offer an integral response through education, victim accompaniment, and cross-sector collaboration. Addressing human trafficking requires more than legal-formal measures; it demands a comprehensive ethical strategy to restore human dignity.